ANALISIN EFEKTIVITAS PENJUAL KOPI KELILING DI DEPAN PARKIRAN UINSU - Adinda Zahwa; Aisyah Putri Arimbi; Aisyah Azzahro Nasution; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effectiveness of mobile coffee vendors operating around the UINSU campus area, particularly in Amaliyun near Yuki Simpang Raya. Mobile coffee vendors represent an informal micro-enterprise that grows by utilizing consumer mobility. This research employs a qualitative descriptive method with a field study approach. Data were collected through direct observation, interviews with vendors, and simple documentation related to operating hours and sales targets. The results show that the vendors set a minimum sales target of 30 cups per day with operating hours from 9:00 a.m. to 7:00 p.m. The strategic location and long operating hours make the business relatively effective in reaching consumers. However, business effectiveness is still influenced by weather conditions, crowd levels, and competition. The study concludes that mobile coffee vending has strong economic potential when managed consistently.